Influence of cerium content on the corrosion behavior of Al-Co-Ce amorphous alloys in 0.6 M NaCl solution. Issue 7 (July 2019) - Zhang, L.M.; Zhang, S.D.; Ma, A.L.; Umoh, A.J.; Hu, H.X.; Zheng, Y.G.; Yang, B.J.; Wang, J.Q.
Abstract: The effect of cerium content on the corrosion behavior of Al-Co-Ce amorphous alloys in 0.6 M NaCl solution was investigated by cyclic polarization, Mott-Schottky and X-ray photoelectron spectroscopy techniques. Results indicated that the open circuit potential of Al-Co-Ce amorphous alloys displayed a decreased tendency with the increase in Ce content, and the amorphous alloy with 4 at.% Ce presented both the lowest passive current density and donor density indicating the best corrosion resistance, while adding excess Ce led to the reduced corrosion resistance of Al-Co-Ce alloys. Furthermore, it was found that a low Ce content is beneficial to the formation of a more protective passive film on Al-Co-Ce amorphous alloys, and the corrosion inhibition reactions of Al-Co-Ce alloys in 0.6 M NaCl solution were changed with the increase in Ce content and the detailed reasons were discussed.